2022
DOI: 10.3389/fnhum.2022.876935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise on the Cognitive Function of Older Patients With Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: BackgroundAging and type 2 diabetes mellitus (T2DM) are important risk factors for the development of cognitive deterioration and dementia. The objective of this research was to investigate the effects of an exercise intervention on cognitive function in older T2DM patients.MethodsEight literature databases (PubMed, EBSCO, Scopus, Embase, The Cochrane Library, Web of Science, Ovid, and ProQuest) were searched from inception to 20 January 2022. The researchers examined randomized controlled trials (RCTs) that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…Memory performance was associated with body composition changes in previous studies in T2D [ 45 ]. Strategies to improve both cardiorespiratory fitness and cognition have been proposed, such as exercise training [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Memory performance was associated with body composition changes in previous studies in T2D [ 45 ]. Strategies to improve both cardiorespiratory fitness and cognition have been proposed, such as exercise training [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both longer and short sleep duration were associated with higher risks of cognitive impairment (27). Doing exercise have positive effect on improving cognitive function (8,28). An umbrella review evaluated 28,205 participants with mild cognitive impairment or dementia, physical activity was not only effective in improving global cognition in Alzheimer disease and in all types of dementia, but also improved noncognitive outcomes in people with dementia including falls, and neuropsychiatric symptoms (8).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that physical activity is beneficial in improving global cognitive function (8,28). An Updated Umbrella Review of the 2018 Physical Activity Guidelines Advisory Committee Report suggested that physical activity improved sleep in adults with insomnia symptoms or obstructive sleep apnea (29).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, meta-analyses have found that exercise significantly improves global cognitive function in elderly patients with T2D. 13 But the evidence in cognitive subdomains is limited and inconsistent. 14 15 PA levels differ between male and female with T2D.…”
Section: Introductionmentioning
confidence: 99%